SISTEM CERDAS PEMBERI PAKAN HAMSTER BERBASIS IoT (INTERNET of THINGS) MENGGUNAKAN METODE NAÏVE BAYES PADA PLATFORM NODE-RED - Rian Hermawan; Nova Silviya (STMIK SUBANG, 2020)
Hamsters are rodents that have nocturnal properties, which means they are habitats that serve hamster activity that occurs at night. Caring for hamsters is not as easy as other people think. Several things need attention, one of which is to feed hamsters. Hamster feeding equipment that can be controlled and monitored remotely via an accessible internet network, allows hamsters to eat regularly, so the owner of the hamster can leave without worry. With the creation of an IoT (Internet of Things) based hamster feeding system using the Naïve Bayes method on the Node-Red platform, hamster owners can control hamster feeding remotely. The results obtained from this study are that the IoT-based animal feeder tool can be used by hamster keepers who are working far away or those who are busy and don't pay much attention to offering hamster feed.